1993
DOI: 10.1523/jneurosci.13-03-00914.1993
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids regulate brain hippocampal 5-HT1A receptor mRNA expression

Abstract: Using in situ hybridization techniques, the expression of 5-HT1A receptor mRNA was measured within the hippocampal formation after bilateral adrenalectomy (ADX). After 24 hr ADX, 5-HT1A receptor mRNA expression was significantly increased in all hippocampal subfields in ADX animals relative to sham-operated controls (SHAM). The magnitude of the increase was most pronounced within CA2 (127%) and CA3/4 (94%)-subfields of dorsal hippocampus, intermediate in the dentate gyrus (73%), and least within CA1 (60%). Adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
2
2

Year Published

1994
1994
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(117 citation statements)
references
References 33 publications
7
106
2
2
Order By: Relevance
“…The present studies were designed to investigate the effect of dexamethasone administration on hip pocampal5-HT1A receptor modulation. In agreement with previous experiments (Mendelson and McEwen 1992;Chalmers et al 1993), the present data indicate that hippocampal 5-HT1A receptor mRNA expression and 5-HT1A binding are sensitive to circulating corti costeroid levels. One week ADX treatment induced large increases in 5-HT1A mRNA abundance across hippocampal subfields.…”
Section: Discussionsupporting
confidence: 93%
“…The present studies were designed to investigate the effect of dexamethasone administration on hip pocampal5-HT1A receptor modulation. In agreement with previous experiments (Mendelson and McEwen 1992;Chalmers et al 1993), the present data indicate that hippocampal 5-HT1A receptor mRNA expression and 5-HT1A binding are sensitive to circulating corti costeroid levels. One week ADX treatment induced large increases in 5-HT1A mRNA abundance across hippocampal subfields.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, corticosteroids have been shown to alter several elements of serotonergic neurotransmission. The removal of circulating corticosteroids by adrenalectomy resulted in anatomically specific decreases in the indices of 5-HT metabolism (Chalmers et al, 1993;De Kloet et al, 1982;Zhong and Ciaranello, 1995). It is therefore likely that the increased ACTH and corticosterone levels observed in the present study after 2 weeks of fluoxetine treatment do not result from changes in HPA activity, but rather reflect a direct effect on pituitary cells caused by increased levels of serotonin.…”
Section: Discussionmentioning
confidence: 54%
“…Autoradiographic studies first identified increased 5-HT 1A receptor binding in the rat hippocampus after adrenalectomy (Biegon et al, 1985). Subsequent investigations have confirmed the sensitivity of 5-HT 1A receptors to circulating corticosteroid levels (Chalmers et al, 1993(Chalmers et al, , 1994Zhong and Ciaranello, 1995). However, the fact that in the present study, plasma ACTH and corticosterone levels were found to be elevated after 2 weeks whereas hippocampal 5-HT 1A mRNA was upregulated after 8 weeks indicates that differential or delayed regulatory mechanisms are operating to adjust limbic 5-HT 1A receptor number during fluoxetine treatment.…”
Section: Discussionmentioning
confidence: 92%
“…A considerable body of evidence suggests that 5HT may stimulate the production of neurons in the dentate gyrus. First, conditions that are associated with diminished granule cell genesis, such as malnutrition (Debassio et al 1996), aging (Kuhn et al 1996;Gould et al 1999), high corticosterone (Cameron and Gould 1994), stress , and NMDA receptor activation (Cameron et al 1995), also decrease the density of 5HT fibers or 5HT1A receptors, or inhibit the release of 5HT in the dentate gyrus (Blatt et al 1994;Chalmers et al 1993;McKittrick et al 1995;Nishimura et al 1995;Meijer and deKloet 1994;Watanabe et al 1993;Tao and Auerbach 1996;Whitton et al 1994;Nyakas et al 1997). Second, experimental manipulations that stimulate granule cell genesis, such as seizures (Parent et al 1997), adrenalectomy (Cameron and Gould 1994), and NMDA receptor antagonist treatment (Cameron et al 1995), also increase the density of 5HT1A receptors or the release of 5HT in the dentate gyrus (Hayakawa et al 1994;Burnet et al 1995;Whitton et al 1994;Kuroda et al 1994).…”
Section: Serotoninmentioning
confidence: 99%